BOOK REVIEW: Ștefan Afloroaei, ‟Privind altfel lumea celor absurde. Experienţe ce descoperă o altă libertatea şi deopotrivă, limitele înţelegerii noastre”, Editura Humanitas, Bucureşti, 2013 - Vasile Cătălin BOBB (Studia Universitatis Babeș-Bolyai. Philosophia)
Lev Şestov does not appear in any page of Ştefan Afloroaei’s latest book, Privind altfel lumea celor absurde (Taking a Different Glance at the Absurd) , but it seems to me that his approach stands under the same logic as the one of the Russian philosopher. Precisely, the revelations in front of death are similar to the ones of thought towards his own limitations; similar in the sense of the method (approach), not of the conclusion (the end result): something completely different happens when facing death; something completely different happens when thought meets its limitations. I would stop the analogy between Şestov and Afloroaei here, especially due to the ultimatum-like feature which the thought of death brings with itself, but I would keep the similarity of the approach: Şestov shows us how thinking, with its limitations, cannot reflect on death, and it demands other frameworks from itself (it does not matter, here, what kinds of frameworks are in question), as long as Afloroaei shows us how the limitations of thought (the nonsense, the lack of sense, the paradox and the ab-surd) transmit something different, completely different, to us, than what they usually seem to tell us.